Studies on parathyroid function in diabetic hemodialysis patients - Inoue, Seishi; Fujita, Yoshikazu; Hirabayashi, Toshiaki; Azuma, Masayuki (Journal of Japanese Society for Dialysis Therapy, 1992)
In general, diabetic dialysis patients (DM-HD) infrequently develop secondary hyperparathyroidism (2°HPT). In order to clarify parathyroid function in DM-HD patients, we investigated several baseline parameters of Ca metabolism in 30 DM and 30 non-DM patients and observed the PTH release induced by acute hypocalcemia during Ca-free HD in 5 DM and 6 non-DM-HD groups. In studying the baseline level, the DM-HD group consisted of 19 males and 11 females, mean age 59.8 years, with dialysis periods of 12.6 months on average. The non-DM group consisted of 16 males and 14 females, mean age 54.6 years and with dialysis periods of 15.7 months. The two groups showed similar levels of Ca, Pi and Al-P, but C-PTH levels were lower in the DM-HD (1.7±1.5ng/ml) in comparison with the non-DM (3.6±2.3ng/ml). There were no significant correlations among PTH, age and dialysis period, but there were significant correlations between PTH and serum P levels in the DM-HD group (r=0.51, p<0.05) and between PTH and serum Ca in the non-DM-HD group (r=-0.59, p<0.05). In the Ca-free HD study, 2 groups showed similar decreases in serum Ca and similar increments in Intact-PTH (ΔIntact-PTH) from baseline. However, because of lower PTH levels, the area under the curve in the DM-HD group was smaller than in the non-DM-HD group. In conclusion, we confirmed lower baseline PTH levels in the DM-HD, but the PTH response to hypocalcemic stimulation is well maintained, and we speculate that basal PTH secretion may be suppressed in the diabetic state through a cell membrane abnormality.